Understanding leadership paradigms and cases - Avery, Gayle 1947-
In Part One of this title, Gayle Avery integrates a fragmented field into four broad paradigms or forms of leadership, helping to simplify and clarify the ill-defined field of leadership. Part Two provides 10 case studies from leading organizations across Europe, Australia and the USA.
Keywords: Leadership; Führung; Fallstudiensammlung